Phylogenetic species of paracoccidioides spp. Isolated from clinical and environmental samples in a hyperendemic area of paracoccidioidomycosis in Southeastern Brazil - Cocio, Tiago A.; Nascimento, Erika; Kress, Marcia R. von Zeska; Bagagli, Eduardo [UNESP]; Martinez, Roberto (MDPI, 2020)
Paracoccidioides brasiliensis complex and P. lutzii are the etiological agents of paracoccidioidomycosis. The geographic distribution of these species in South America is still poorly comprehended. Fifty samples of Paracoccidioides spp. were genotyped, with 46 clinical isolates predominantly isolated in the geographic area of Ribeirão Preto, SP, and four environmental isolates collected in Ibiá, MG, southeastern Brazil. These isolates were evaluated by PCR-RFLP (Restriction Fragment Length Polymorphism) of the tub1 gene and the sequencing of the gp43 exon 2 loci. The species P. lutzii was confirmed by sequencing the internal transcribed spacer (ITS) region of the ribosomal DNA. P. brasiliensis sensu stricto S1b (n = 42) and S1a (n = 5), P. americana (n = 1), P. restrepiensis (n = 1), and P. lutzii (n = 1) were identified among the clinical isolates. All the environmental isolates were characterized as P. brasiliensis sensu stricto S1b. The patient infection by P. lutzii, P. americana (PS2), and one isolate of P. brasiliensis sensu stricto S1b most likely occurred in a geographic area far from the fungal isolation site. No association was found between the infecting genotype and the disease form. These results expand the knowledge of the Paracoccidioides species distribution and emphasize that human migration must also be considered to pinpoint the genotypes in the endemic area.
Keywords: Eco-epidemiology; Paracoccidioides americana (PS2); Paracoccidioides restrepiensis (PS3); Paracoccidioidomycosis; Paracoccidoides brasiliensis sensu stricto (S1a and S1b); Paracoccidoides lutzii